2006
DOI: 10.1103/physrevlett.96.134505
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Two-Phase Flow Patterns at a Simple Junction in Microfluidic Devices

Abstract: We study the behavior of a confined stream made of two immiscible fluids when it reaches a T junction. Two flow patterns are witnessed: the stream is either directed in only one sidearm, yielding a preferential flow pathway for the dispersed phase, or splits between both. We show that the selection of these patterns is not triggered by the shape of the junction nor by capillary effects, but results from confinement. It can be anticipated in terms of the hydrodynamic properties of the flow. A simple model yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…We show that the size of the loop is an important parameter. In the large-loop situation, i.e., when the two arms are at least six times longer than the bubble size, as shown in previous studies [4][5][6][7][8][9][10][11][12][13], we evidence a filtering and a transition regime. Strikingly and contrary to previous studies [9,[14][15][16][17] in the repartition regime situation, we point out that the hydrodynamic resistances or the total flow rates are never equal in the two arms.…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…We show that the size of the loop is an important parameter. In the large-loop situation, i.e., when the two arms are at least six times longer than the bubble size, as shown in previous studies [4][5][6][7][8][9][10][11][12][13], we evidence a filtering and a transition regime. Strikingly and contrary to previous studies [9,[14][15][16][17] in the repartition regime situation, we point out that the hydrodynamic resistances or the total flow rates are never equal in the two arms.…”
Section: Introductionsupporting
confidence: 84%
“…Strikingly and contrary to previous studies [9,[14][15][16][17] in the repartition regime situation, we point out that the hydrodynamic resistances or the total flow rates are never equal in the two arms. We note that this point was suggested by Engl [6] but not evidenced experimentally. In this new regime where interactions between bubbles cannot be neglected, we show that for low and moderate bubble densities, the continuous phase flow rates are equal in the two arms.…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…Gas bubbles and reagent-filled aqueous drops are alternately formed at a microfluidic T-junction and subsequently assemble downstream into an ordered foam lattice (Movie M2 in Supporting Information). , The injected gas periodically clears reagents from the T-junction, thereby preventing reagent buildup and nanoparticle deposition that occurs when laminar fluid streams are left undisturbed. , These features are a significant advance over current droplet-based microfluidic synthesis methods, where droplet formation is sensitive to fluid properties such as interfacial tension, and downstream droplet coalescence is a frequent occurrence …”
Section: Resultsmentioning
confidence: 99%
“…For example, bubbles and droplets can breakup or do not breakup at the T‐junction, depending mainly on their sizes and the capillary number . For the nonbreaking case, repartition and filtering regimes are observed, owing to the flow rates in the arms of the junctions . Jeanneret et al recently focused on the transport of particles in one‐dimensional loop networks and showed that the dynamics is asymptotically invariant upon time‐reversal symmetry.…”
Section: Introductionmentioning
confidence: 99%